Contribution of Leg Explosive Power and Reaction Speed to 100-meter Running Speed - Hanafi, Suriah; Amahoru, Nurul Musfira (Journal of Sport Education, Coaching, and Health (JOCCA), 2023)
This research is descriptive research with a correlational design. This study aims to find out: (1). Is there a contribution of leg explosive power to the ability to run 100 meters in students of SMP Negeri 24 Makassar, (2). Is there a contribution of foot reaction speed to 100-meter running ability, (3). Is there a contribution of leg explosive power and foot reaction speed to the ability to run 100 meters in students of SMP Negeri 24 Makassar? The population is students of SMP Negeri 24 Makassar, the number of samples is 30 people using random sampling techniques. The analysis technique used is regression and correlation analysis through the SPSS application program version 22.00 with a significant level of 0.05 α. The results showed that: (1) There was a significant contribution of leg explosive power to the ability to run 100 meters in students of SMP Negeri 24 Makassar, amounting to 55.7%. (2) There was a significant contribution of foot reaction speed to the ability to run 100 meters in students of SMP Negeri 24 Makassar, amounting to 51.7%. (3) There is a significant contribution of leg explosive power and foot reaction speed to the ability to run 100 meters in students of SMP Negeri 24 Makassar, amounting to 64.5%.